2019
DOI: 10.1002/hbm.24822
|View full text |Cite
|
Sign up to set email alerts
|

Altered resting‐state functional connectivity within the developing social brain after pediatric traumatic brain injury

Abstract: Traumatic brain injury (TBI) in childhood and adolescence can interrupt expected development, compromise the integrity of the social brain network (SBN) and impact social skills. Yet, no study has investigated functional alterations of the SBN following pediatric TBI. This study explored functional connectivity within the SBN following TBI in two independent adolescent samples. First, 14 adolescents with mild complex, moderate or severe TBI and 16 typically developing controls (TDC) underwent resting-state fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 84 publications
(119 reference statements)
1
9
0
Order By: Relevance
“…Fusiform gyrus is part of the temporal and occipital lobes, which has been found to be a key structure for high-order visual (such as face, body and high special frequency objects) and imagery processing [68, 69]. Functional brain activation and connectivity studies in children with TBI have also reported fusiform gyrus-related abnormalities, such as reduced activations during sustained attention processing [18], significantly increased activation during working memory processing [7], and altered functional connectivity between fusiform gyrus and frontal lobe during resting state [21]. On the other hand, studies have demonstrated significant involvement of the fusiform gyrus in severe psychopathology, especially psychosocial and emotional dysregulation and thought problems in patients with Major Depression Disorder [70, 71], Schizophrenia [72, 73], and other mental disorders [74, 75].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusiform gyrus is part of the temporal and occipital lobes, which has been found to be a key structure for high-order visual (such as face, body and high special frequency objects) and imagery processing [68, 69]. Functional brain activation and connectivity studies in children with TBI have also reported fusiform gyrus-related abnormalities, such as reduced activations during sustained attention processing [18], significantly increased activation during working memory processing [7], and altered functional connectivity between fusiform gyrus and frontal lobe during resting state [21]. On the other hand, studies have demonstrated significant involvement of the fusiform gyrus in severe psychopathology, especially psychosocial and emotional dysregulation and thought problems in patients with Major Depression Disorder [70, 71], Schizophrenia [72, 73], and other mental disorders [74, 75].…”
Section: Discussionmentioning
confidence: 99%
“…Resting-state fMRI (rs-fMRI) studies in TBI have also reported inconsistent results. Relative to matched controls, children with chronic TBI have been found to have reduced functional connectivity (FC) between caudate and motor network [20], increased FC between frontal and fusiform gyrus [21], or reduced FC between rostral anterior cingulate cortex and amygdala [22]. In addition, graph theoretical technique (GTT)-based rs-fMRI studies have reported systems-level topological alterations in adults with TBI, relative to controls [23].…”
Section: Introductionmentioning
confidence: 99%
“…Resting-state fMRI (rs-fMRI) studies in TBI have also reported inconsistent results. Relative to matched controls, children with chronic TBI have been found to have reduced functional connectivity (FC) between caudate and motor network [24], increased FC between the frontal and fusiform gyrus [25], or reduced FC between rostral anterior cingulate cortex and amygdala [26]. In addition, graph theoretical technique (GTT)-based rs-fMRI studies have reported system-level topological alterations in adults with TBI, relative to controls [27].…”
Section: Introductionmentioning
confidence: 99%
“…Disruption to any of these neurobiological processes can alter the development of functional and structural connections that are necessary for complex adaptive behaviors. Indeed, pediatric TBI has been linked to white matter alterations in the corpus callosum (Ewing-Cobbs et al, 2008) via neural vasculature changes (Wendel et al, 2019) as well as altered functional connectivity of social processing networks (Tuerk et al, 2019) years after injury, suggesting that pediatric TBI contributes to lasting alterations in behaviorally relevant brain structure and function.…”
Section: Introductionmentioning
confidence: 99%